Cooperation between parents and teachers - systemic solutions proposals - Anna Gulczyńska (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
The aim of the article is to give some systemic approach proposal as a base to educational offer. Poor relation between parents and teachers at Polish schools is a fact. Political and social-cultural changes, or taking into consideration different criteria - globalization and digitalization changes, caused transformation of parents - teachers relations. According to recent research, they are dissatisfying, rare, disappointing and frustrating for both parties. They are not an important element of school politics for directors of educational institutions. It is worth to start changes at local level, they may in the future cause global changes - in this case meaning countrywide changes. Good practices must be based on good theories.